The Effectiveness of Audio Visual Media on the Learners’ Skill in Writing Fable Text 1 - Elpi Zulita; Sukarno Sukarno; Bustomi Bustomi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
This research was intended to determine the frequency of the effectiveness of audio-visual media towards the first grade students of SMP Negeri 1 Kaur in learning fable texts. To reveal these problems in depth and thoroughly, this research was designed by using the true experimental method using Post Test Only Control Design. The results of the study showed that the implementation of using audio-visual media in writing fable texts by class VII A obtained an average score of 75.38 while writing fable texts without using audio-visual media by class VII B SMP Negeri 1 Kaur obtained an average score of 65.96. The result showed that the implementation of Audio visual media in writing fable text was effective. It could be proven through the calculation of t-test which obtained thitung > ttabel = 2,738 > 2,056. In this case, there was a significant difference in using audio-visual media without using audio-visual media on the students’ skill in writing fable text by class VII A and VII B SMP Negeri 1 Kaur. Audio-visual media could be deemed effective for the students in learning fable texts better.